Analysis of the level of interest and level of taxpayer satisfaction with the quality of service at the East Belitung Samsat Office - Tri Astuti Ramadhani Haliza; Lukas Purwoto; Etty Puji Lestari (Studies in Economy and Public Policy, 2025)
Purpose: This study examines whether there is a gap between taxpayers’ perceived importance and satisfaction with services at the East Belitung Samsat Office. This study focuses on evaluating the service quality dimensions tangibles, reliability, responsiveness, assurance, and empathy to determine whether the services provided align with public expectations. Research methodology: The study employed a survey approach with a sample of 100 respondents selected through quota sampling, representing taxpayers who had received services at the Samsat Office. Secondary data, including employee profiles and statistical data on the number of taxpayers, were also used. The analysis applied The Wilcoxon Test was used to compare the perceived importance of each service dimension with the actual satisfaction level reported by respondents. Results: The Wilcoxon test analysis demonstrated a statistically significant difference between importance and satisfaction across all five dimensions of service quality. This indicates that although taxpayers consider the services important, their actual experience with the services provided has not yet reached the expected standards. Conclusion: The study concludes that the quality of services at the East Belitung Samsat Office does not fully meet taxpayers’ expectations, as significant service gaps were identified. Limitations: This research is constrained by its sample size of only 100 respondents, obtained through quota sampling, which may not adequately represent the broader taxpayer population of East Belitung. Contribution: This study contributes to the application of the SERVQUAL model in public sector services and provides valuable insights into service quality evaluation within the Indonesian tax administration context.